In vivo effects of 3, 4-methylenedioxymethamphetamine (MDMA) and its deuterated form in rodents: Drug discrimination and thermoregulation. (1st March 2020) - Berquist, Michael D.; Leth-Petersen, Sebastian; Kristensen, Jesper Langgaard; Fantegrossi, William E.
Abstract: Background: Recent clinical studies support the use of 3, 4-methylenedioxymethamphetamine (MDMA) as an adjunct treatment for posttraumatic stress disorder (PTSD). Despite these promising findings, MDMA administration in controlled settings can increase blood pressure, heart rate, and body temperature. Previous studies indicate that O -demethylated metabolites of MDMA contribute to its adverse effects. As such, limiting the conversion of MDMA to reactive metabolites may mitigate some of its adverse effects and potentially improve its safety profile for therapeutic use. Methods: We compared the interoceptive and hyperthermic effects of a deuterium-substituted form of MDMA (d2-MDMA) to MDMA using rodent drug discrimination and biotelemetry procedures, respectively. Results: Compared to MDMA, d2-MDMA produced full substitution for a 1.5 mg/kg MDMA training stimulus with equal potency and effectiveness in the drug discrimination experiment. In addition, d2-MDMA produced increases in body temperature that were shorter-lasting and of lower magnitude compared to equivalent doses of MDMA. Last, d2-MDMA and MDMA were equally effective in reversing the hypothermic effects of the selective 5-HT2A/2C antagonist ketanserin. Conclusion: These findings indicate that deuterium substitution of hydrogen at the methylenedioxy ring moiety does not impact MDMA's interoceptive effects, and compared to MDMA, d2-MDMA has less potential for producing hyperthermic effects and likely has similar pharmacodynamic properties. Given that d2-MDMA produces less adverse effects than MDMA, but retains similar desirable effects that are thought to relate to the effective treatment of PTSD, additional investigations into its effects on cardiovascular functioning and pharmacokinetic properties are warranted.